Linguistic Clues to Support the Hypotesis that Archbishop Berenguel de Landoira Promoted the Composition of Miragres de Santiago - Mariño Paz, Ramón (Madrygal. Revista de Estudios Gallegos, 2025)
Miragres of Santiago is a Galician work transmitted by a manuscript that can be dated between 1390 and 1420. It contains a very neglected copy of a work prepared previously. Due to the importance that the stories of the life of Santiago the Minor and the transfer of his head to Santiago de Compostela have in it, some art historians have pointed out that its writing must have been promoted by Berenguel de Landoira, archbishop of Santiago from 1317 to 1330, who in 1322 ordered to make a reliquary for the head of the said apostle, or by Juan García de Manrique, archbishop between 1383 and 1388, who enriched that reliquary and took other measures aimed at relaunching the cult of this saint. In this article I make an analysis of nine linguistic variables in which I gather data that can support the hypothesis that the work was promoted during the archbishopric of Berenguel de Landoira. Probably, he ordered the inclusion of the stories related to Santiago the Minor within the framework of the book that we know as Miragres de Santiago, and not the writing of an autonomous Liber Sancti Iacobi Minoris. Only in two of the variables I have explored did I detect data that could suggest for the stories of the Epiphany and the Ascension a later date than for the rest of the work.